1996
DOI: 10.1136/ard.55.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide.

Abstract: Nitric oxide is a gas generally known by its chemical formula NO, or NO. The dot denotes an unpaired electron, which is the definition of a free radical; pbssessing this, NO is highly reactive and quite -different from the anaesthetic agent nitrous oxide (N20), which is extremely stable. Until recently, NO was best known as a constituent of car exhaust fumes, contributing to the photochemical smog of cities such as Los Angeles. In contrast, the work which crucially altered this perception was performed in a le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 231 publications
(24 reference statements)
1
61
0
2
Order By: Relevance
“…A molécula do NO tem um elétron não pareado e reage facilmente com oxigênio, radical superóxido, ou metais de transição, como ferro, cobalto, manganês ou cobre 6 . O NO tem alta afinidade com o heme, encontrado em proteínas intracelulares (óxido nítrico-sintase, cicloxigenase e guanilato ciclase) e também liga-se a grupos -SH, formando tiol 10 ; é um gás incolor e estável, moderadamente solúvel em água e sua meiavida varia de 3 a 60 segundos, mas pode ser maior devido ao ambiente do NO, concentração de O 2 e O· 2 - 6,[11][12][13][14][15][16] . Parece que o NO exerce maior efeito na imunidade inespecífica do que na específica, exibindo atividade citostática ou citocida contra uma notável amplitude de microorganismos patogênicos 8,17 .…”
Section: Introductionunclassified
“…A molécula do NO tem um elétron não pareado e reage facilmente com oxigênio, radical superóxido, ou metais de transição, como ferro, cobalto, manganês ou cobre 6 . O NO tem alta afinidade com o heme, encontrado em proteínas intracelulares (óxido nítrico-sintase, cicloxigenase e guanilato ciclase) e também liga-se a grupos -SH, formando tiol 10 ; é um gás incolor e estável, moderadamente solúvel em água e sua meiavida varia de 3 a 60 segundos, mas pode ser maior devido ao ambiente do NO, concentração de O 2 e O· 2 - 6,[11][12][13][14][15][16] . Parece que o NO exerce maior efeito na imunidade inespecífica do que na específica, exibindo atividade citostática ou citocida contra uma notável amplitude de microorganismos patogênicos 8,17 .…”
Section: Introductionunclassified
“…They are rapidly activated by intracellular Ca 2+ fluxes and produce small quantities of NO. Inducible NOS (type II) is a Ca 2+ -independent isoform and can be induced in many cells including hepatocytes, macrophages, neutrophils, smooth muscle cells and chondrocytes by cytokines and endotoxin during inflammatory and infectious processes and generates large amounts of NO [5, 6, 7]. NO has been implicated in a variety of biological processes such as the relaxation of vascular smooth muscle cells, neurotransmission, immunity and inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%
“…NO has been implicated in a variety of biological processes such as the relaxation of vascular smooth muscle cells, neurotransmission, immunity and inflammatory processes. NO has also been postulated in several pathological processes related to immunological, cardiovascular and neurological disorders, infections and cancer [6]. Determination of the NO radical itself is difficult because of its radical nature and very short half-life.…”
Section: Introductionmentioning
confidence: 99%
“…Type II is a Ca 2+ -independent isoform that can be induced in large amounts by cytokines and endotoxins during inflammatory or infectious processes in many cells, including hepatocytes, macrophages, neutrophils, smooth muscle cells and chondrocytes. NO derived from eNOS has been implicated in a variety of biological processes such as relaxation of vascular smooth muscle cells, which causes vasodilatation and an anticoagulant effect [5,6]. On the other hand, it has been shown that oxidized low-density lipoprotein decreases the expression of eNOS [7].…”
Section: Introductionmentioning
confidence: 99%